Delayed surgery for acute type A aortic dissection: a retrospective review of an alternative surgical strategy in the COVID-19 era - Rin Itokawa; Ryosuke Kowatari; Yuki Imamura; Hanae Sasaki; Norihiro Kondo; Kazuyuki Daitoku; Masahito Minakawa (Journal of Cardiothoracic Surgery, 2024)
Abstract Background During the coronavirus disease (COVID-19) pandemic, medical resources have often been limited to emergency surgeries. This study aimed to evaluate our experience with delayed surgery for acute type A aortic dissections (ATAADs). Methods A retrospective study was conducted on 33 patients who underwent surgery for ATAADs between January 2020 and December 2021. The patients were divided into two groups: patients treated within 12 h of arrival (E group; N = 21) and those treated > 12 h after arrival (D group; N = 12) with strict antihypertensive therapy until surgery. Results The plasma fibrinogen levels on arrival were lower in the D group than in the E group (174.3 ± 109.1 vs 293.4 ± 165.4, p = 0.038). The time to surgery from symptom onset was longer in the D group than in the E group (4 ± 1 h vs. 86 ± 108 h, p < 0.001). There was one case (3%) of mortality and seven cases (21%) of cerebral infarctions in the E group. There was no significant difference in the intraoperative data and quantity of blood transfused between the two groups. Conclusion Thus, delayed surgery for ATAAD with appropriate preoperative management may be an alternative surgical strategy in the COVID-19 era.